Hydrologic soil study of an alpine watershed - Dourojeanni, Axel Charles, author; Meiman, James R. (James Richard), advisor; Dils, Robert E., committee member; Schumm, S. A., committee member (Colorado State University. Libraries, 1969)
A 2.3 Km^2 (0.89 sq. mi.) alpine watershed in the Colorado Front Range is partitioned into 13 hydrologic units. This partitioning is based on generic soil type, landforms, steepness of slope, and aspect. Most of the variation in hydrologic properties is reflected in the delineation of the major soil types. Water storage in the top 1 m of soil is the major soil hydrologic property considered. Strip terraces, alluvial terraces and the concave central area are the zones with the highest water storage capacity in the watershed (average of 44 cm/m depth). The total water storage capacity of the watershed to a depth of 1 m was calculated as 6,401 x 10^2 m3 (ac-ft). Total water storage capacity in the top 1 m is inversely related to landform slope: considering all soils, the correlation coefficient is 0.84; for the podzols, 0.91. A coefficient of correlation of 0.89 exists between bulk density and detention storage capacity. Hydraulic conductivity of selected soils ranges, in the upper horizons, from 67 cm/hr in podzol and alpine meadow soils to 16 cm/hr in lithosols and alpine turf soils. Hydraulic conductivity of all four soils decreases to 2 to 3 cm/hr at 50 to 100 cm depth.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Soil science; Hydrology; Watersheds